Office ergonomics practical applications - McKeown, Céline (CRC Press, 2008)
Although many modern offices have invested significantly in ergonomics, there is a lack of consideration for smaller issues, such as type of footrest and position of computer mouse, that are perceived as less important. This text addresses the potential negative impact of such issues.